Turnover Intention PT. Efrata Retailindo Ditinjau dari Beban Kerja, Lingkungan Kerja dan Kepuasan Kerja - Esti Khomaryah; Supawi Pawenang; Sholichul Hadi A.B (Universitas Muria Kudus, 2020)
Turnover is a level of employee exit in a company. Turnover is influenced by factors such as workload, work environment and job satisfaction. This research aims to determine the impact of workload, work environment and job satisfaction on turnover intention. Sampling technique of simple random sampling is used in this research. The data was taken directly using a questionnaire distributed to 88 respondents of PT. Efrata Retailindo Surakarta employees. The method of analysis used in this study is multiple linear regression. The results showed that workload, work environment, and job satisfaction have influence on turnover simultaneously. Workload and work environments have a positive and significant impact on turnover while job satisfaction has negative and significant impact on turnover.